Extra status and extra stress: Are promotions good for us? - David W. Johnston; Wang-Sheng Lee (Institute for the Study of Labor (IZA), 2012)
Promotions ordinarily involve higher wages and greater privileges; but they also often involve increased responsibility, accountability and work hours. Therefore, whether promotions are good for workers' wellbeing is an empirical question. Using high-quality panel data we estimate pre- and post-promotion effects on job attributes, physical health, mental health and life satisfaction, in an attempt at answering this question. We find that promotions substantially improve job security, pay perceptions and overall job satisfaction in the short term, and that promotions have short and longer term effects on job control, job stress, income and hours worked. However, despite these large effects on job attributes, we find that promotions have negligible effects on workers' health and happiness. Only mental health seems affected, with estimates suggesting significant deterioration two years after receiving a promotion. Thus, it seems the additional stress involved with promotions eventually outweighs the additional status, at least for the average worker.
Keywords: I0; I31; J62; 330; promotion; status; stress; job satisfaction; Erwerbsverlauf; Erwerbsstatus; Stress; Arbeitszufriedenheit; Schätzung; Australien